Superplastic deformation of the AK4-1 alloy with a surface layer melted by electron pulse beam - Bryukhovetsky, V.V.; Poyda, A.V.; Poyda, V.P.; Milaya, D.E. (Вопросы атомной науки и техники, 2019)
Specimens of the aluminum alloy AK4-1, previously irradiated by a pulsed electron beam, are deformed under the conditions of superplasticity. The features of structural changes in the course of superplastic deformation of preirradiated specimens are studied. It is shown that the deformation processes occurring in the main part of the specimen and in the layer, melted by a pulsed electron beam, have fundamental differences. Зразки алюмінієвого сплаву АК4-1, попередньо опромінені імпульсним пучком електронів, були продеформовані в умовах надпластичності. Вивчено особливості структурних змін у ході надпластичної деформації попередньо опромінених зразків. Показано, що деформаційні процеси, що відбуваються в основній частині зразка і в переплавленому імпульсним пучком електронів шарі, мають принципові відмінності. Образцы алюминиевого сплава АК4-1, предварительно облученные импульсным пучком электронов, были продеформированы в условиях сверхпластичности. Изучены особенности структурных изменений в ходе сверхпластической деформации предварительно облученных образцов. Показано, что деформационные процессы, происходящие в основной части образца и в переплавленном импульсным пучком электронов слое, имеют принципиальные различия.